A look of the contributions of the methodological strategies in learning biology - Pereira-Chaves, José (2015)
Teaching Biology, from the point of view of mandatory learning for high school students, has become a major challenge for teachers of this discipline. Therefore, the actions carried out in the classroom to mediate the content, should be planned with a broad vision of what we want to accomplish with learning.  Due to this, the importance of understanding the processes of teaching and learning of biological concepts in the classroom is crucial for pedagogical mediation. The aim of this study was to document the contributions of the methodological strategies used by the teacher in the learning of Biology. This research was carried out under an ethnographic approach through a case study, observations, interviews, content analysis, and a focus group.  It was evident the concern and commitment of the teacher in the understanding of the biological content, using various methodological strategies by the students, and the encouragement given to them to continue learning.  On the other hand, the students showed motivation in each of the academic activities performed in the classroom.